A catechol biosensor based on electrospun carbon nanofibers - Dawei Li; Zengyuan Pang; Xiaodong Chen; Lei Luo; Yibing Cai; Qufu Wei (Beilstein Journal of Nanotechnology, 2014)
Carbon nanofibers (CNFs) were prepared by combining electrospinning with a high-temperature carbonization technique. And a polyphenol biosensor was fabricated by blending the obtained CNFs with laccase and Nafion. Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscope (FE-SEM) were, respectively, employed to investigate the structures and morphologies of the CNFs and of the mixtures. Cyclic voltammetry and chronoamperometry were employed to study the electrocatalysis of the catechol biosensor. The results indicated that the sensitivity of the biosensor was 41 µA·mM−1, the detection limit was 0.63 µM, the linear range was 1–1310 µM and the response time was within 2 seconds, which excelled most other laccase-based biosensor reported. Furthermore, the biosensor showed good repeatability, reproducibility, stability and tolerance to interferences. This novel biosensor also demonstrated its promising application in detecting catechol in real water samples.